A rare case of esophageal diverticulum with classical presentation - Deepthi, Bekal Tharanath; Seetha Pramila, Varada Venkata; Tyagi, Varsha (Indian Journal of Case Reports, 2018)
Diverticula of the esophagus are rare, accounting for